Identification of Key Gene Signatures Associated With Bone Metastasis in Castration-Resistant Prostate Cancer Using Co-Expression Analysis - Yu, Zhongxiang; Zou, Hanlin; Wang, Huihao; Li, Qi; Yu, Dong (Frontiers in Oncology, 2021)
About 80-90% of castration-resistant prostate cancer (CRPC) patients would develop bone metastasis. However, the molecular mechanisms of bone metastasis are still not clear. This study aimed to detect the differences between the tumor and normal samples in bone after metastatic colonization. 4 transcriptional datasets (GSE32269, GSE101607, GSE29650 and GSE74685) were obtained from the GEO database. 1983 differentially expressed genes (DEGs) were first identified between tumor and normal marrow samples in GSE32269. Most of the top10 up-regulated DEGs are related with prostate cancer, and the top10 down-regulated DEGs are mainly related with bone development. 7 co-expression modules were then detected based on the 1469 DEGs shared by the 4 datasets. 3 of them were found highly preserved among the 4 datasets. Enrichment analysis showed that the three modules were respectively enriched in Cell adhesion molecules (CAMs), Leukocyte transendothelial migration and cell cycle, which might play significant important roles in the tumor development in bone marrow. 10, 17 and 99 hub genes for each module were then identified. And 4 genes (C3AR1, IL10RA, LY86 and MS4A6A) were detect to be tightly related to progression of bone metastatic CRPC. ROC curve was plotted and AUC was calculated to distinguish tumor and normal bone marrow samples as well as bone and non-bone metastatic CRPCs. The present study identified key genes and modules involved in bone metastatic CRPCs, which may provide new insights and biomarkers for understanding of the molecular mechanisms of bone metastatic CRPC.